Intra‐operative assessment of left‐sided colorectal anastomotic integrity: a systematic review of available techniques. (25th October 2020) - Clifford, Rachael E.; Fowler, Hayley; Manu, Nicola; Sutton, Paul; Vimalachandran, Dale
Abstract: Aim: Anastomotic leak (AL) after colorectal resection is associated with increased rates of morbidity and mortality: potential permanent stoma formation, increased local recurrence, reduced cancer‐related survival, poor functional outcomes and associated quality of life. Techniques to reduce leak rates are therefore highly sought. Method: A literature search was performed for published full text articles using PubMed, Cochrane and Scopus databases with a focus on colorectal surgery 1990–2020. Additional papers were detected by scanning references of relevant papers. Results: A total of 53 papers were included after a thorough literature search. Techniques assessed included leak tests, endoscopy, perfusion assessment and fluorescence studies. Air‐leak testing remains the most commonly used method across Europe, due to ease of reproducibility and low cost. There is no evidence that this reduces the leak rate; however, identification of a leak intra‐operatively provides the opportunity for either suture reinforcement or formal takedown with or without re‐do of the anastomosis and consideration of diversion. Suture repair alone of a positive air‐leak test is associated with an increased AL rate. The use of fluorescence studies to guide the site of anastomosis has demonstrated reduced leak rates in distal anastomoses, is safe, feasible and has a promising future. Conclusion: Although over reliance on any assessment tool should be avoided, intra‐operative techniques with the aim of reducing AL rates are increasingly being employed. Standardization of these methods is imperative for routine use. However, in the interim it is recommended that all anastomoses should be assessed intra‐operatively for mechanical failure, particularly distal anastomoses.